Population Genomics of a Cosmopolitan Weed Provides Insights Into Its Local Adaptation and Recent Demographic History - Marilia Souza Lucas; Christoph Rosche; Isabell Hensen; Stefan G. Michalski; Dávid U. Nagy; Diana Gamba; Renske E. Onstein; Karime Abidkulova; Mohammad Al‐Gharaibeh; Ali A. Al‐Namazi; Sirwan Babaei; Fernando Bastida; et al. (Molecular Ecology, 2026)
Invasive plant species present a growing ecological and economic challenge, and often adapt rapidly to their novel environments through complex demographic and evolutionary processes. Invasion genomics offers powerful tools to disentangle these processes, but most studies rely on geographically narrow sampling across native and non‐native ranges. Erigeron canadensis is a cosmopolitan weed native to North America that has successfully invaded diverse climates worldwide. We used double‐digest restriction site‐associated DNA sequencing (ddRADseq) to investigate the genetic diversity and structure of 280 E. canadensis populations across the Northern Hemisphere. We found that native and non‐native populations maintained comparable genetic diversity. Population structure analyses revealed four genetic clusters that were mainly differentiated along latitudinal and aridity gradients. However, one cluster was strongly overrepresented in the non‐native compared to the native range. In the native range, genetic differentiation was shaped by spatial and environmental gradients, while in non‐native regions human‐mediated dispersal and repeated introductions disrupted environmentally driven genetic structure. Migration network analyses revealed limited intercontinental connectivity and a possible role of long‐distance dispersal in within‐range expansions. Genomic offset analyses showed that genotype‐environment mismatches in non‐native populations associated with reduced growth and reproduction. Together, our results indicate that the invasion dynamics of E. canadensis were driven by multiple introductions, population admixture, and lineage sorting, while some genotypes contributed disproportionately to the spread of this invader. The presence of apparent maladaptation suggests that even long‐established invaders may still be evolving in response to their novel environment, raising concerns about potential future expansions.

Non-native seeds of Solidago gigantea perform equally well or weaker than native seeds during germination and early seedling growth - Kevin Kožić; Robert W. Pal; Christoph Rosche; Ragan M. Callaway; Kevin Cianfaglione; Aray Dossan; David J. Ensing; Rita Filep; Zigmantas Gudžinskas; Isabell Hensen; Inderjit; Chandra E. Moffat; et al. (Flora, 2026)

Correction to: Together again: the invasive mustard Hesperis matronalis suffers devastating seed predation by a recently adventive specialist weevil - David J. Ensing; Tyler D. Nelson; Chandra E. Moffat; Lauryn Joslin; Lucas Eckert; Marlene M. Kraml; Christopher G. Eckert (BioControl, 2025)

Together again: the invasive mustard Hesperis matronalis suffers devastating seed predation by a recently adventive specialist weevil - David J. Ensing; Tyler D. Nelson; Chandra E. Moffat; Lauryn Joslin; Lucas Eckert; Marlene M. Kraml; Christopher G. Eckert (BioControl, 2025)
The enemy release hypothesis underpins classical (or importation) biocontrol as a management technique for invasive species. Classical biocontrol has had resounding success when prospective control agents have been subject to appropriate screening before release. Occasionally, however, natural enemies have been reunited with their hosts accidentally. Such adventive agents may provide effective control but have also avoided the careful screening characteristic of modern importation biocontrol programmes. We were studying the invasive mustard, Hesperis matronalis L. (Dame’s rocket; Brassicaceae: Hesperidae), when we discovered rampant seed predation by an unknown seed predator. Using DNA barcoding, we identified this seed predator as Ceutorhynchus inaffectatus Gyllenhal (Coleoptera: Curculionidae), a recently (2018) detected species in North America. Comparing potential and realised seed production, we found that seed predation by C. inaffectatus strongly reduces H. matronalis fecundity, and that this effect was not moderated by infection with turnip mosaic virus (TuMV), a commercially important pathogen hosted by H. matronalis and transmitted by polyphagous aphid species. C. inaffectatus is expected to be highly host-specific, and the absence of native Hesperidae species in North America suggests the potential for C. inaffectatus as a classical, but adventive, biocontrol agent of H. matronalis . We suggest population genetic research to identify the origin of C. inaffectatus , and host specificity testing before any intentional redistribution of this species for H. matronalis biocontrol. More generally, this system acts as a model for biocontrol prospects with adventive insect herbivore species.

Phenological sensitivity of Bromus tectorum genotypes depends on current and source environments - Megan L. Vahsen; Toby M. Maxwell; Dana M. Blumenthal; Diana Gamba; Matthew J. Germino; Mevin B. Hooten; Jesse R. Lasky; Elizabeth A. Leger; Nikki Pirtel; Lauren M. Porensky; Seth Romero; Justin J. Van Ee; et al. (Ecology, 2025)
Plants respond to their environment with both short‐term, within‐generation trait plasticity, and long‐term, between‐generation evolutionary changes. However, the relative magnitude of plant responses to short‐ and long‐term changes in the environment remains poorly understood. Shifts in phenological traits can serve as harbingers for responses to environmental change, and both a plant's current and source (i.e., genotype origin) environment can affect plant phenology via plasticity and local adaptation, respectively. To assess the role of current and source environments in explaining variation in flowering phenology of Bromus tectorum , an invasive annual grass, we conducted a replicated common garden experiment using 92 genotypes collected across western North America. Replicates of each genotype were planted in two densities (low = 100 seeds/1 m 2 , high = 100 seeds/0.04 m 2 ) under two different temperature treatments (low = white gravel; high = black gravel; 2.1°C average difference) in a factorial design, replicated across four common garden locations in Idaho and Wyoming, USA. We tested for the effect of current environment (i.e., density treatment, temperature treatment, and common garden location), source environment (i.e., genotype source climate), and their interaction on each plant's flowering phenology. Flowering timing was strongly influenced by a plant's current environment, with plants that experienced warmer current climates and higher densities flowering earlier than those that experienced cooler current climates and lower densities. Genotypes from hot and dry source climates flowered consistently earlier than those from cool and wet source climates, even after accounting for genotype relatedness, suggesting that this genetically based climate cline is a product of natural selection. We found minimal evidence of interactions between current and source environments or genotype‐by‐environment interactions. Phenology was more sensitive to variation in the current climate than to variation in source climate. These results indicate that cheatgrass phenology reflects high levels of plasticity as well as rapid local adaptation. Both processes likely contribute to its current success as a biological invader and its capacity to respond to future environmental change.

Not a melting pot: Plant species aggregate in their non‐native range - Gisela C. Stotz; James F. Cahill; Jonathan A. Bennett; Cameron N. Carlyle; Edward W. Bork; Diana Askarizadeh; Sandor Bartha; Carl Beierkuhnlein; Bazartseren Boldgiv; Leslie Brown; Marcelo Cabido; Giandiego Campetella; et al. (Global Ecology and Biogeography, 2020)
Aim Plant species continue to be moved outside of their native range by human activities. Here, we aim to determine whether, once introduced, plants assimilate into native communities or whether they aggregate, thus forming mosaics of native‐ and alien‐rich communities. Alien species might aggregate in their non‐native range owing to shared habitat preferences, such as their tendency to establish in high‐biomass, species‐poor areas. Location Twenty‐two herbaceous grasslands in 14 countries, mainly in the temperate zone. Time period 2012–2016. Major taxa studied Plants. Methods We used a globally coordinated survey. Within this survey, we found 46 plant species, predominantly from Eurasia, for which we had co‐occurrence data in their native and non‐native ranges. We tested for differences in co‐occurrence patterns of 46 species between their native (home) and non‐native (away) range. We also tested whether species had similar habitat preferences, by testing for differences in total biomass and species richness of the patches that species occupy in their native and non‐native ranges. Results We found the same species to show different patterns of association depending on whether they were in their native or non‐native range. Alien species were negatively associated with native species; instead, they aggregated with other alien species in species‐poor, high‐biomass communities in their non‐native range compared with their native range. Main conclusions The strong differences between the native (home) and non‐native (away) range in species co‐occurrence patterns are evidence that the way in which species associate with resident communities in their non‐native range is not species dependent, but is instead a property of being away from their native range. These results thus highlight that species might undergo important ecological changes when introduced away from their native range. Overall, we show origin‐dependent associations that result in novel communities, in which alien‐rich patches exist within a mosaic of native‐dominated communities.